Soilless Cultivation: Dynamically Changing Chemical Properties and Physical Conditions of Organic Substrates Influence the Plant Phenotype of Lettuce - Nerlich, Annika; Dannehl, Dennis (Frontiers in Plant Science, 2021)
In agriculture, the increasing scarcity of arable land and the increase in extreme weather conditions has led to a large proportion of crops, especially vegetables, being cultivated in protected soilless cultivation methods to provide people with sufficient and high-quality food. Rockwool has been used for decades as a soil substitute in soilless cultivation. Since rockwool is not biodegradable, it is disposed in landfills after its use, which nowadays leads to ecological concerns and drives the search for alternative substrates, especially organic materials. The objectives of this study were to investigate the effects of organic materials (wood chips, sphagnum moss and hemp fibers) in relation to rockwool substrate on plant growth and quality of lettuce as a result of physical and chemical properties of the mentioned substrates. We were able to show that sphagnum moss is a suitable substitute substrate for lettuce cultivation, contrary to hemp. All investigated substrates presented good physical properties, but differed in their decomposition stability. Within 8 weeks, 30% of the hemp and about 10% of both sphagnum and wood materials were degraded.. It was concluded that the increased microbiological activity immobilized nitrogen and led to oxygen deficiency in the rhizosphere and resulted in increased phenolic acid contents in lettuce but poor yield on hemp. Sphagnum caused a pH decrease and accumulation of ammonium in the nutrient solution and allowed the highest yield for lettuce at moderate phenolic acid contents. Low yields were obtained on wood, which could possibly be increased by optimized nutrient solution, so that wood as an alternative to rockwool was not excluded. By applying used organic substrates as soil additives on arable land, the nutrients accumulated in it might fertilize the open field crops, thus saving mineral fertilizers. This, together with the avoidance of waste, would contribute to a greater sustainability.